2005
DOI: 10.1177/0146167204271318
|View full text |Cite
|
Sign up to set email alerts
|

Darwinian Grandparenting: Preferential Investment in More Certain Kin

Abstract: Studies on grandparental investment have revealed that mothers’ fathers are emotionally closer to their grandchildren than are fathers’ mothers. In the current study, it was hypothesized that this difference is caused by the fact that fathers’ mothers often have the potential to invest in genetically more certain kin (children through their daughters). To test this hypothesis, 787 participants rated their emotional closeness and exposure to their grandparents and indicated whether they had cousins through pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 19 publications
5
113
1
2
Order By: Relevance
“…Children being the respondents has its' advantages and disadvantages. Grandparents might not be the ideal source of information, as they may wish to present their involvement as equal in all children (see Euler and Weitzel 1996;Euler et al 2001;Laham et al 2005;Danielsbacka et al 2011) and in this respect the children as a source of information might be more reliable. Although children aged 11-16 years old might not be aware of their grandparents labour force participation, their health or even their age quite accurately, they are still the best information source in the case of complex research frame such as one interested in here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children being the respondents has its' advantages and disadvantages. Grandparents might not be the ideal source of information, as they may wish to present their involvement as equal in all children (see Euler and Weitzel 1996;Euler et al 2001;Laham et al 2005;Danielsbacka et al 2011) and in this respect the children as a source of information might be more reliable. Although children aged 11-16 years old might not be aware of their grandparents labour force participation, their health or even their age quite accurately, they are still the best information source in the case of complex research frame such as one interested in here.…”
Section: Discussionmentioning
confidence: 99%
“…One of the strongest predictions is the order of grandparents (1) maternal grandmother, (2) maternal grandfather, (3) paternal grandmother, (4) paternal grandfather which is due to the paternity uncertainty and preferential investment in more certain kin (see, e.g. Laham et al 2005;Danielsbacka et al 2011). According to evolutionary theory and its emphasis on the sex and the lineage we may form following predictions about the relevant connections between different variables and grandparental involvement.…”
Section: Evolutionary Theory Perspectivementioning
confidence: 99%
“…We can thus concur that differences in the ascribed role of grandmothers do not account for grandparental solicitude as observed in contact frequencies. Such a difference can be explained by co-residence of grandparents (see GAULIN et al 1997;MCBURNEY et al 2002 but see EULER andWEITZEL 1996), sex-specific investment (EULER and WEITZEL 1996;EULER and MICHALSKI, in press) or the availability of alternative investment outlets (LAHAM et al 2005). Contrary to MICHALSKI and SHACKELFORD (2005), we find consistent differences in contact frequency not only between MGM and PGF but also between other comparisons (MGM vs. PGM; MGF vs. PGM; MGF vs. PGF).…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary studies of grandparental investment in modern societies have mainly focussed on retrospective ratings by grandchildren, rather than grandparental behaviour (CHRASTIL et al 2006;EULER and WEITZEL 1996;EULER, HOIER and ROHDE 2001;LAHAM, GONSALKORALE and VON HIPPEL 2005;PASHOS 2000;but see MICHALSKI and SHACKELFORD 2005). The main argument for using this method has been that grandparents would give socially desirable answers and therefore would claim to treat all grandchildren equally (EULER and WEITZEL 1996;HOFFMAN 1979HOFFMAN -1980.…”
Section: Introductionmentioning
confidence: 99%
“…Even before Smith, researchers with no evolutionary overview had reported that American children feel closer, on average, to their MGMs than to their PGMs (e.g., Kahana and Kahana, 1970;Hoffman, 1980;Hartshorne and Manaster, 1982), and after Smith, studies in several countries have replicated his frequency of contact results (e.g., Eisenberg, 1988;Uhlenberg and Hammill, 1998;Laham et al, 2005), and/or demonstrated other sorts of biased engagement and investment favoring the maternal side (e.g., Eisenberg, 1988;Tyszkowa, 1991;Boon and Brussoni, 1996;Euler and Weitzel, 1996;Salmon, 1999;Dubas, 2001;Chrastil et al, 2006;Pashos and McBurney, 2008;Bishop et al, 2009;Kirchengast and Putz, 2016).…”
Section: Grandmothering In Modern Democraciesmentioning
confidence: 99%